COL1A1, PRPF40A, and UCP2 correlate with hypoxia markers in non-small cell lung cancer - Oleksiewicz, Urszula (J Cancer Res Clin Oncol, 2017)
PURPOSE: Collagen 1A1 (COL1A1), RNA-binding and pre-mRNA Processing Factor (PRPF40A), and Uncoupling Protein 2 (UCP2) were identified as downstream effectors of cytoglobin (CYGB), which was shown implicated in tumour biology. Although these three genes have been previously associated with cancer, little is known about their status in lung malignancies. METHODS: Hereby, we investigated the expression and promoter methylation of COL1A1, PRPF40A, and UCP2 in 156 non-small cell lung cancer (NSCLC) and adjacent normal tissues. RESULTS: We demonstrate that COL1A1 and PRPF40A mRNAs are significantly overexpressed in NSCLC (p < 1 × 10(−4)), while UCP2 exhibits a trend of upregulation (p = 0.066). Only COL1A1 promoter revealed hypermethylation in NSCLCs (36%), which was particularly evident in squamous cell carcinomas (p = 0.024) and in the tumours with moderate-to-good differentiation (p = 0.01). Transcript level of COL1A1, as well as PRPF40A and UCP2, exhibited striking association (p ≤ 0.001) with the expression of hypoxia markers. In addition, we demonstrate in lung cancer cell lines exposed to hypoxia or oxidative stress that COL1A1 transcription significantly responds to oxygen depletion, while other genes showed the modest upregulation in stress conditions. CONCLUSION: In conclusion, our data revealed that COL1A1, UCP2, and PRPF40A are novel players implicated in the complex network of hypoxia response in NSCLC.